FOREIGN LANGUAGE LEARNING DEVELOPMENT: REFLECTIONS ON THE CONTRIBUTION OF DIGITAL TECH-NOLOGY (Revista de Letras Norte@mentos, 2019)
Recently, the advent of technology has affected teaching and learning languages. In this context, opportunities have arisen, especially with various digital technologies available, which have allowed learners to experience the learning process in different ways and with more resources. Considering this trend, studies have been concerned with reflections on the use of digital tech-nology for the processes of teaching and learning foreign language (L2). This study has the objective of presenting three digital resources, namely webconferencing, digital games and digi-tal stories, as well as telecollaboration. In addition, it aims at discussing how these digital re-sources can contribute to L2 learning development.